Twenty years of climate policy: G20 coverage and gaps. (7th February 2022) - Nascimento, Leonardo; Kuramochi, Takeshi; Iacobuta, Gabriela; den Elzen, Michel; Fekete, Hanna; Weishaupt, Marie; van Soest, Heleen Laura; Roelfsema, Mark; Vivero-Serrano, Gustavo De; Lui, Swithin; Hans, Frederic; Jose de Villafranca Casas, Maria; et al.
ABSTRACT: The number and coverage of climate change mitigation policies have increased in the past twenty years, but important policy adoption gaps remain. To analyse sectoral climate policy in the G20 over time (2000–2019), we compiled a dataset of climate change mitigation-relevant policies and identified 50 key policy options that constitute a comprehensive sectoral climate policy package. Approximately half of these policy options are not widely adopted. Adoption is particularly low for policies that aim to: phase out coal and oil and mandate energy reductions in electricity and heat supply; reduce industrial process emissions and incentivise fuel switch in industry; design urban planning strategies for retrofits; and support the use of renewable energy for cooking and heating/cooling purposes in buildings. Policies to remove fossil fuel subsidies and support carbon dioxide removal also need substantial improvement. However, many policy adoption gaps exist as the coverage of at least one policy option could be improved in each sector. Policy adoption gaps leave at least one-tenth of the G20's emissions completely uncovered. Filling these gaps is fundamental to realize the full mitigation potential of existing policy options and to advance the transition towards global net zero greenhouse gas emissions. Key policy insights: Mitigation-related policy options can be presented as a matrix by sector to shed light on what constitutes a comprehensive climate policy package; looking across sectoral climate policies helps to unpack and clarify the status of adoption. Policy adoption gaps exist in all sectors. Increasing the sectoral coverage of climate policies will help to ensure that all relevant sectoral emissions and mitigation areas are considered in national mitigation efforts. Even if an increase in policy coverage alone does not ensure emission reductions, the absence of policy coverage indicates that emissions can still be further reduced and that a portion of global emissions remain uncovered by policies. Despite the observed increase in the number and coverage of climate policies, slow progress towards reducing global emissions and meeting the collective Paris climate goals calls for more comprehensive climate change mitigation policies. Filling policy adoption gaps presents a concrete strategy to improve sectoral, national and global climate policy.